Magnetic tio2- achored silica carbon composite nanofibers for enhanced photocatalytic oxidation of acid orange 7 - Sie, Xin Yi (2014)
In this study, a magnetically separable nanostructured photocatalyst, TiO2/Fe3O4/SiO2/CNF, constituting of titanium dioxide (TiO2) nanosheets anchored on silica-carbon composite nanofibres, was prepared for enhanced photocatalytic oxidation (PCO). The issue of recycling in application of nanostructured TiO2 was addressed by imparting the sample with magnetic property through Fe3O4. Incorporation of anatase phase TiO2 nanosheets (TiO2-NSs) is successfully done through a facile solvothermal method combined with post-calcination in nitrogen gas, resulting in the construction of uniform sheaths of anatase TiO2-NSs on a composite carbon nanofiber backbone. This product was characterized in terms of the surface morphology, phase purity, chemical composition, thermal stability, pore properties and specific surface area using Field Emission Scanning Electron Microscopy (FE-SEM), X–ray powder diffraction (XRD), Energy Dispersive X-ray (EDX), Thermogravimetric Analysis (TGA) and N2 adsorption-desorption isotherms. The photocatalytic performance of the prepared composite was assessed by the PCO of Acid orange 7 dye as a representation pollutant, under ultraviolet (UV) illumination. From the UV-vis absorption spectrum and further calculation, it is revealed that the synthesised sample TiO2/Fe3O4/SiO2/CNF (Fe3O4 = 28.3 wt %) had the best PCO efficiency after 2 h of irradiation, superior to that of industrial Degussa P25. Plausible explanation and mechanisms for the enhanced ability were predicted and discussed. The magnetic separation of the Fe loaded photocatalyst was also demonstrated to display its efficiency in the recovery process.